Proses Sita Jaminan Di Dalam Pengadilan Negeri Terhadap Debitur Wanprestasi - Amiliya; Eka Barokah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
. In an agreement made between one individual and another individual, an agreement will be created between the two parties regarding matters that will be agreed upon by both parties, where the agreement must be fulfilled by one or both of them. In a debt and receivables agreement, a debtor if If you fail to fulfill your performance, creditors are required to compensate for the losses they have caused with movable or immovable objects they own, where previously creditors who felt aggrieved were required to submit an application for confiscation of collateral in the District Court, where confiscation of collateral was a confiscation carried out by the District Court of goods. movable or immovable belonging to the defendant or plaintiff to ensure that goods during the examination process at trial are not transferred to be used as collateral for repayment. So this research will focus on the actual process of confiscating collateral carried out by the District Court for debtors who have been declared in default